2012
DOI: 10.1111/gbb.12006
|View full text |Cite
|
Sign up to set email alerts
|

Sensation‐seeking genes and physical activity in youth

Abstract: Many studies examining genetic influences on physical activity (PA) have evaluated the impact of single nucleotide polymorphisms (SNPs) related to the development of lifestyle-related chronic diseases, under the hypothesis that they would be associated with PA. However, PA is a multi-determined behavior and associated with a multitude of health consequences. Thus, examining a broader range of candidate genes associated with a boarder range of PA correlates may provide new insights into the genetic underpinning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 71 publications
(108 reference statements)
1
23
1
Order By: Relevance
“…However, among participants in our cohort of Mexican heritage youth, we observed a moderate inverse association between linguistic acculturation and participation in community sports [13]. Consistent with this finding, although not significantly different, a higher proportion of youth born in Mexico participated in at least 60 minutes of PA on five days out of seven compared to youth born in the U.S [14]. In addition, we observed clear sex-specific effects among youth who are not highly acculturated, as more boys than girls were more likely to meet PA standards [15].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, among participants in our cohort of Mexican heritage youth, we observed a moderate inverse association between linguistic acculturation and participation in community sports [13]. Consistent with this finding, although not significantly different, a higher proportion of youth born in Mexico participated in at least 60 minutes of PA on five days out of seven compared to youth born in the U.S [14]. In addition, we observed clear sex-specific effects among youth who are not highly acculturated, as more boys than girls were more likely to meet PA standards [15].…”
Section: Introductionsupporting
confidence: 71%
“…In our previous work in this cohort, adolescents who met PA standards reported higher levels of thrill and adventure seeking than their peers who did not meet PA standards [15], before and after adjustment for genetic variance associated with sensation-seeking [14]. In the current analysis, the association between thrill and adventure seeking and PA was stronger for youth born in Mexico compared to youth born in the U.S.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A genetic influence of exercise behavior may be easily detected during the younger period. On the other hand, a previous study, that examined associations between PA level and 630 SNPs in genes related to the dopamine, serotonin, opioid, and cannabinoid pathways, showed that several SNPs were associated with PA 31) . Many polymorphisms are related to complex traits, such as exercise behavior or PA level, and the environment surrounding individuals also affects them.…”
Section: Conflict Of Interestsmentioning
confidence: 92%
“…It has been reported that there were no significant associations between DRD2/ANKK1 TaqIA polymorphism (rs1800497) and current PA level 30,31) or current exercise habit 19) . These results, derived from a subjective assessment of PA only in youth or post-menopausal women using a questionnaire, were consistent with those of the present study wherein an objective questionnaire was used for PA assessment.…”
Section: Conflict Of Interestsmentioning
confidence: 99%